Analysis of age, height, and weight measures among weightlifters from different countries - Draga, V.; Hiskia, G.; Mochernjuk, V (2001)
Weight greatly depends on age and height. One, of course, becomes heavier with age. Several famous sportsmen, such as the Olympic champions, Naim Suleymanoglu, Anatoli Khrapaty, Nicu Vlad, and Leonid Taranenko considerably increased their body weight during the sports career (1980-2000).